The Relationship Between Hospitality And Outpatient Loyalty Of The Sawah Besar Health Center - Lia Noviyanti; Harahap, Sarah Geltri; Ludovikus, Ludovikus (Sean Institute, 2024)
Hospitality is defined as a service full of hospitality and warmth provided by health care providers to patients. The purpose of this study is to find out the relationship between hospitality and outpatient loyalty at the Sawah Besar Health Center. This research method uses a quantitative cross sectional study. The population in this study is outpatients with a sample of 150 respondents where the respondents are patients who have been treated more than once at the Sawah Besar Health Center. Data analysis was carried out univariate to see the picture and bivariate to see the relationship. The results of the study showed that public hospitality with a good category of 95.3% and poor as much as 4.7%, personal hospitality was good 92%, poor 8%, therapeutic hospitality was good 92.7% and poor 7.3%. In addition, the results of this study show that there is a relationship between hospitality, namely public, personal, and therapeutic hospitality and outpatient loyalty at the Sawah Besar Health Center in 2023, which shows a P value of <0.05. Most of the respondents in this study stated that they were good for these three hospitality and loyal to the health center, although there were still some complaints. It is recommended that health centers should continue to improve hospitality services to patients.